Sanksi Hukum Pelaku Kekerasan dalam Rumah Tangga - Syamsiah (Universitas Islam Indragiri, 2024)
Domestic violence is also known as domestic violence, which is gender-based and personal. In this research, the author uses library research methods sourced from previous books and journals. The main issues in this study are (1) What is meant by domestic violence, (2) Criminal sanctions for perpetrators of domestic violence, (3) the role of the government in preventing cases of domestic violence and (4) the negative impact on victims of domestic violence. This study concludes that domestic violence is an act committed against someone, especially women, which causes suffering and misery physically, sexually, psychologically and domestic neglect. The criminal provisions in articles 44 to 53 where sufficient sanctions include physical violence that is classified as severe, which causes someone to fall ill or seriously injured, it will be imprisoned for a maximum of ten years and if it causes the victim to die, it will be subject to a maximum imprisonment of fifteen years and also includes physical, psychological and sexual violence that causes the victim to not recover, lose memory and abort or die in the womb, it will be subject to criminal sanctions in the form of twenty years imprisonment. While the role of the government in domestic violence prevention efforts is to formulate, policy, communication, information, education and socialization and advocacy to the community, and the impact of victims of domestic violence is in the form of physical and mental where the physical impact is in the form of headaches, nausea, memory loss, loss of consciousness, bruises and mental impact is in the form of shame, depression, stress, helplessness and confusion, decreased self-confidence and self-esteem, suicide attempts and anxiety disorders.